KEBIJAKAN PENDIDIKAN DI ERA REVOLUSI 4.0: GAMIFIKASI PENDIDIKAN, MENGUBAH VIDEO GAME MENJADI PLATFORM - Deding Ishak (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2019)
Several previous studies have found that gamification can be a very helpful tool in increasing student effectiveness in learning. But unfortunately, the application of gamification is still very limited. As a result, teachers are still hesitant to adopt games as a teaching tool because of the limiting factors, such as the complexity of the game, the complexity of adapting to the desired results, the lack of student involvement and the difficulty of incorporating it into the learning curriculum. This study uses data from various previous studies, to then be analyzed and found conclusions. The results of the research then show that the game as an educational platform must have a character in the form of being able to adapt to various educational goals; provide access for teachers to be able to control student engagement; increase and decrease the level of difficulty to be able to maintain the desired level of complexity; and maintain student interest by balancing the difficulty level with the student's ability level.